english: english - Roy Jodi Martin Pohan; Dewi Iryani; Puguh Aji Haris Setiawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The use of third-party collateral in loan agreements is a common practice in Indonesia, yet it becomes legally complex when the principal debtor is declared bankrupt. This research examines the legal status of third-party collateral and the scope of the curator's authority in bankruptcy proceedings under Articles 55–60 of Law No. 37 of 2004, focusing on the interpretation of the phrase "the object serving as collateral" in Article 59(2) and the accountability obligations imposed on secured creditors under Article 60(1). This study employs a normative juridical method with statutory, conceptual, and case approaches, using Decision No. 9/Pdt.Sus-GLL/2024/PN.Niaga.Jkt.Pst as the primary case study. The findings indicate that although collateral owned by third parties is not part of the bankruptcy estate, the curator retains substitutive authority to liquidate such collateral when the secured creditor fails to execute its rights within the prescribed time limit. This authority does not extinguish the third party's ownership rights; proceeds from the sale must first satisfy the secured creditor's claim, and any surplus must be returned to the owner. The obligation of accountability under Article 60(1) demonstrates that the execution of secured rights affects the value of claims previously registered by the secured creditor with the curator, thereby establishing a structural relationship between secured rights and accountability obligations. The 2024 decision affirms that the curator's act of listing and coordinating third-party collateral does not constitute an unlawful act, provided it is conducted for orderly and accountable liquidation purposes. Accordingly, harmonizing the rights of secured creditors, the supervisory authority of the curator, and the protection of collateral owners is essential for establishing legal certainty in Indonesian bankruptcy practice.